Nauczyciel edukacji wczesnoszkolnej przewodnikiem dziecka wkraczającego w świat muzyki - Kisiel, Mirosław (Nauczyciel wczesnej edukacji: Rozwijanie kompetencji zawodowych, 2016)
The competencies of early childhood education teacher viewed from the perspective of music education are the main theme of the article. The work depicts a child raised as the recipient of music. There are dilemmas affecting problems with music education in the early grades of primary school. On the basis of the obtained test results there is shown an overview of the elementary music teacher’s competencies viewed through the prism of the neglected areas and aspects that deserve to be popularized as positive manifestations in this regard.